Changes in working memory performance and cortical activity during acute aerobic exercise in young adults - Zheng, Kefeng; Deng, Zhangyan; Qian, Jiali; Chen, Yanxia; Li, Shiyuan; Huang, Tao (Frontiers in Behavioral Neuroscience, 2022)
This study aimed to examine the concurrent performance of working memory and cortical activation during an acute bout of aerobic exercise in young adults. In a crossover study design, 27 young adults (mean age = 22.7 ± 3.4 years, 56% females) underwent two experimental conditions in a randomized order: (1) sitting condition; (2) cycling condition. Working memory was measured by modified versions of the n-back task. Cortical activation was monitored using a multi-channel functional near-infrared spectroscopy (fNIRS) system. Reaction time (RT) of n-back task was significantly faster in the cycling condition (p < 0.05). No differences in the accuracy were observed between sitting and cycling conditions. fNIRS results showed that the oxygenated hemoglobin (oxy-Hb) concentrations in bilateral frontopolar area (p < 0.05), dorsolateral prefrontal cortex (p < 0.05), and right pre-motor and supplementary cortex (p < 0.05) were decreased in the cycling condition. The findings indicated that the concurrent performance of working memory was improved during moderate intensity exercise, whereas cortical activation was decreased in some brain regions.